Attitudes toward CSR : the attitudes of Finnish trade unions' representatives toward corporate social responsibility practices - Pietiläinen, Ella (2015)
The aim of this study was to investigate the attitudes of trade union representatives toward companies’ CSR practices. The research participants were representatives of altogether nine Finnish trade unions and one Finnish solidarity centre representing the trade unions. The data had been collected as part of a bigger research project concerning trade unions and CSR but this study is an independent research using the same data. Altogether 206 pages of transcribed data gathered through interviews were analysed. The data was analysed with content analysis, and the aim was to be objective and code the data in a quantitative as well as qualitative form. The theoretical framework for this study followed Fishbein and Ajzen’s (2010) theory of planned behaviour (TPB). TPB was not used in its original form but it was adopted with some exceptions to fit better into this study. Other theoretical themes were corporate social responsibility as the leading theme and national business systems as the interpretative contextual factor for trade unions. Also the connections between these two themes in former studies were discussed. Based on the results it is suggested that trade union representatives evaluate CSR practices in three main ways, namely negatively, neutrally and positively. The attitudes were divided into twelve groups to provide a more detailed description of the topic. Cynical attitudes have four subgroups, attitudes of restriction have three subgroups and proactive attitudes have five subgroups. The dominating attitude was attitude of restriction “Companies act under pressure”, and the least occurred attitude subgroups were the proactive attitude groups.